The foreign encounter in myth and religion - Pijl, Kees van der (Pijl, Kees van der. Modes of foreign relations and political economy, 2010)
The author traces the key characteristics of 'foreign encounters' over time, showing that myth, religion and ethical philosophies have always informed the way that societies have interacted with outsiders.